2019
DOI: 10.1186/s13568-019-0785-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of gold nanoparticles derived from mannosylerythritol lipid and evaluation of their bioactivities

Abstract: In this study, we introduce a simple and green method for synthesis of gold nanoparticles (AuNPs) using microbial glycolipid mannosylerythritol lipid (MEL) produced from Ustilago maydis CGMCC 5.203 and to evaluate their biomedical activities. MEL was found 10.3 g/L using sunflower oil. The formation of MEL-AuNPs was verified using UV–visible spectrum, XRD, TEM, FTIR, SEM, and EDX. In the biomedical examinations, MEL-AuNPs demonstrated potential cytotoxicity against HepG2 cells, and IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 37 publications
(44 reference statements)
1
21
1
Order By: Relevance
“…The appearance of these peaks undisputedly demonstrates the successful formation of AuNPs in AuNPs‐HG‐1 . Notably, the reflection peak at 38.23° has higher intensity than other reflection peaks at 44.38°, 64.52°, and 77.55°, showing good accordance with the previous reports . The estimation of crystalline size ( D ) of AuNPs‐HG‐1 was then conducted by using Debye–Scherrer equation [ D = (0.9 λ )/ β cos θ ] that reveals the relationship between diffraction peaks broadening and crystalline size .…”
Section: Resultssupporting
confidence: 78%
“…The appearance of these peaks undisputedly demonstrates the successful formation of AuNPs in AuNPs‐HG‐1 . Notably, the reflection peak at 38.23° has higher intensity than other reflection peaks at 44.38°, 64.52°, and 77.55°, showing good accordance with the previous reports . The estimation of crystalline size ( D ) of AuNPs‐HG‐1 was then conducted by using Debye–Scherrer equation [ D = (0.9 λ )/ β cos θ ] that reveals the relationship between diffraction peaks broadening and crystalline size .…”
Section: Resultssupporting
confidence: 78%
“…Our previous researches also revealed that MEL-A has significantly inhibited the growth of Bacillus cereus [12] and Staphylococcus aureus [13] . Expect for its intrinsic capacity, MELs have been a key part of nanoparticles as emulsifier, exhibiting potent inhibitive effect on pathogens [30] , [31] , [32] . However, the abuse of antibiotics resulted in the emergence of methicillin-resistant Staphylococcus aureus (MRSA), which can survive in severe environment and convey a novel challenge to anti-infective treatments [33] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that MELs play a crucial role in the rapid biosynthesis of metallic nanoparticles and enhance the antimicrobial property, yet the underlying mechanism of inhibition still needs further study. metallic nanomaterials including silver, zinc oxide, and gold nanoparticles mediated by MEL-A, and all of them exert inhibitory efficacy against pathogenic gram-positive and gram-negative bacteria [104]. These findings indicated that MELs play a crucial role in the rapid biosynthesis of metallic nanoparticles and enhance the antimicrobial property, yet the underlying mechanism of inhibition still needs further study.…”
Section: Glycolipid-modified Materials 31 Nanocompositesmentioning
confidence: 95%